Work and Labor in Slow-Progressive Sectors of the Economy - Vuorensyrjä, Matti (Nordic Journal of Working Life Studies, 2013)
In the late 1960s, William Baumol demonstrated that structurally unbalanced growth, with the associated cost disease phenomenon, can be expected to have some very particular effects on work and labor in slow-progressive sectors of the economy: performing arts, health care, education, and law enforcement. Specifically, there will be downward pressure on the rate of growth of unit wages and upward pressure on the rate of growth of productivity in these sectors. In the long run, the effects of cost disease are potentially damaging for work and labor in some of the key human service occupations in the public sector. In this interdisciplinary paper, we put forward a simple model, which reconstructs and renews the model discovered by Baumol in 1967. Our model makes only a minor modification to Baumol’s original cost disease model, but the implications of this modification are noteworthy. They are also largely unexplored in empirical research. In this paper, we search for empirical traces of the effects of cost disease on work and labor. We use earlier economic and social scientific research literature on inter-industry wage differences and on time pressure, and we analyze differences in work orientations with the help of the ISSP Work Orientations III data set. Our empirical findings are early and rough intimations. However, they do give preliminary support to the propositions of the paper. The observed changes in employment, wages, and experienced time pressure all correspond to what we would expect on the basis of the cost disease hypothesis. The same applies to the observed differences in the structure of incentives across different occupational groups. The paper is not empirically conclusive, but we see it as a basis for interesting further research.